Application of Social Media in Crisis Management Advanced Sciences and Technologies for Security Applications - Akhgar, Babak; Staniforth, Andrew; Waddington, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book explores how social media and its advances enables citizens to empower themselves during a crisis. The book addresses the key issues related to crises management and social media as the new platform to assist citizens and first responders dealing with multiple forms of crisis, from major terrorist attacks, larger scale public disorder, large-scale movement of people across borders, and natural disasters. The book is based on the results and knowledge gained during the European Commission ATHENA project which has been addressing critical issues in contemporary crisis management and social media and smart mobile communications. This book is authored by a mix of global contributors from across the landscape of academia, emergency response and experts in government policy and private industry. This title explores and explains that during a modern crisis, the public self-organizes into voluntary groups, adapt quickly to changing circumstances, emerge as leaders and experts and perform life-saving actions; and that they are increasingly reliant upon the use of new communications media to do it. • Explores how socio-technical developments have enabled citizen-based response during times of crisis and disaster; • Discusses how to facilitate the inclusion of emergent technological initiatives into organizational structures; • Features contributions from academia and practitioners, exploring the state of art in social media deployment in crisis management.
Introduction -- Section I: Human Factors and Recommendations for Best Practice -- Human Factors in Crisis, Disaster and Emergency: Some Policy Im-plications and Lessons of Effective Communication -- Crisis Management, Social Media and Smart Devices -- Case Studies in Crisis Communication: Some Pointers to Best Practice -- Section II: Technological Design and Development of ATHENA -- Best Practices in the Design of a Citizen-Focused Crisis Management Platform -- Analyzing Crowd-Sourced Information and Social Media for Crisis Management -- The Athena Mobile Application -- Standardization to Deal with Multi-lingual Information in Social Me-dia During Large-scale Crisis Situations -- Cloud-based Intelligence Acquisition and Processing for Crisis Man-agement -- Section III: Salient Legal Considerations -- The Relevant Legal Framework -- Legal Considerations Relating to the Police Use of Social Media -- Section IV: Testing and Evaluating the ATHENA System -- Preliminary ATHENA Case Studies: Test-bed Development and De-livery -- The Final Athena Test Case: West Yorkshire Police Training and Development Centre, Wakefield (UK), September 2016 -- Concluding remarks -- Index.
Keywords: Telecommunication; Security systems; Computer networks .; Industrial organization; Social media; Communications Engineering, Networks; Security Science and Technology; Computer Communication Networks; Organization; Social Media